Balanced volatile sedation with isoflurane in critically ill patients with aneurysmal subarachnoid hemorrhage – a retrospective observational study - Müller, Martin B.; Terpolilli, Nicole A.; Schwarzmaier, Susanne M.; Briegel, Josef; Huge, Volker (Frontiers in Neurology, 2023)
Introduction In patients with severe aneurysmal subarachnoid hemorrhage (SAH) deep sedation is often used early in the course of the disease in order to control brain edema formation and thus intracranial hypertension. However, some patients do not reach an adequate sedation depth despite high doses of common intravenous sedatives. Balanced sedation protocols incorporating low-dose volatile isoflurane administration might improve insufficient sedation depth in these patients. Methods We retrospectively analyzed ICU patients with severe aneurysmal SAH who received isoflurane in addition to intravenous anesthetics in order to improve insufficient sedation depth. Routinely recorded data from neuromonitoring, laboratory and hemodynamic parameters were compared before and up to 6 days after initiation of isoflurane. Results Sedation depth measured using the bispectral index improved in thirty-six SAH patients (−15.16; p = 0.005) who received additional isoflurane for a mean period of 9.73 ± 7.56 days. Initiation of isoflurane sedation caused a decline in mean arterial pressure (−4.67 mmHg; p = 0.014) and cerebral perfusion pressure (−4.21 mmHg; p = 0.013) which had to be balanced by increased doses of vasopressors. Patients required increased minute ventilation in order to adjust for the increase in PaCO2 (+2.90 mmHg; p < 0.001). We did not detect significant increases in mean intracranial pressure. However, isoflurane therapy had to be terminated prematurely in 25% of the patients after a median of 30 h due to episodes of intracranial hypertension or refractory hypercapnia. Discussion A balanced sedation protocol including isoflurane is feasible for SAH patients experiencing inadequately shallow sedation. However, therapy should be restricted to patients without impaired lung function, hemodynamic instability and impending intracranial hypertension.